Analysis of Factors Affecting Indonesian Cocoa Beans Supply, Demand, and Exports - Huda, Safira; Widayanti, Sri; Syah, Mirza Andrian (MediaTrend, 2025)
This study aims to analyze the factors affecting domestic supply, domestic demand, and exports of cocoa beans in Indonesia. The model in this study used simultaneous equations with the analysis method in the form of Two Stage Least Square (2SLS). This research uses secondary data with a time period of 2006 - 2021. The results of this study explain that:(1) Domestic cocoa bean supply is influenced by domestic cocoa bean prices, domestic coffee bean prices, productivity levels, exports, and the previous year’s supply. (2) Domestic demand for cocoa beans is influenced by domestic cocoa bean prices, domestic coffee bean prices, exports, and the previous year’s demand. (3) Cocoa bean exports are influenced by international prices, exchange rates, domestic cocoa bean supply, and domestic cocoa bean demand. The results of this study are expected to contribute to policy recommendations for the government to maximize the supply, demand, and export of cocoa beans. The limitations of this study lie in the fact that the data was collected via the internet and sourced from several different publications, which may have led to discrepancies in the data for the same year.